Middle East Peace Prospects After Abraham Accords - Khan, Salman Ali (Journal of Pakistan Administration, 2021)
The recognition of Israel by Arab states has brought tectonic shift in policies of countries, such as, UAE and Bahrain, and is likely to change the political landscape of the Middle-East which would have far-reaching implications for the region and beyond. On September 15, 2020, Prime Minister of Israel Benjamin Netanyahu and the Foreign Ministers of United Arab Emirates and Bahrain, Abdullah bin Zayed Al Nahyan and Abdullatif AlZayani, respectively, signed a general declaration of principles which was called “The Abraham Accords”. The ceremony was hosted and presided by the President of the United States of America, Donald Trump. The document was also signed by the President Trump while taking credit for brokering a deal through the Middle East Peace Plan, also known as Trump’s Peace Plan. Abraham Accords Peace Agreement was a treaty of peace and normalization of diplomatic relations between the state of Israel and the two Arab states UAE and Bahrain. The U.A.E. and Bahrain are the third and fourth Arab countries to open diplomatic relations with Israel recently; Egypt (1979) and Jordan (1994) were the first two.
Keywords: Middle East; Peace Prospects; Abraham; UAE; Bahrain